Equality Education in Prisons: Youth Detention Centre Model - Rumiari Rumiari; Ach Rasyad; Endang Sri Rejeki; Abdul latif bustami (Ianna Journal of Interdisciplinary Studies)
Background: Education is a means for humans to grow, according to their inherent abilities and the environment they inhabit, to discover their true identity. The success of education and skills depends on the choice of learning approach, one that is experiential without an emphasis on learning. Education and skills provide opportunities for adolescents and adults in prisons to develop knowledge and skills.